A new trusteeship? : the international administration of war-torn territories - Caplan, Richard (Adelphi papers ;, 2002)
This paper analyses and assesses the effectiveness of international administrations of war-torn territories and discusses the key issues - strategic, political, and economic - that arise in the context of these experiences. It reflects on the policy implications of these experiences and recommends reforms or new approaches to international administration.